Competency Analysis of the Role of Pacitan District Teacher Activists in Cooperation with Pacitan District Local Government - Heri Nurdiyanto; Edi Istiyono; Galih Pranowo; Ririn Susetyaningsih (Journal of Research in Social Science and Humanities, 2025)
This study examines the competencies of teacher activists in Pacitan District, focusing on their roles and collaborations with the local government to enhance educational development. Teacher activists, often representing key stakeholders in the educational ecosystem, play a pivotal role in shaping policies, implementing educational reforms, and fostering a collaborative spirit with government agencies. The study investigates the skill sets, knowledge, and personal attributes that define effective teacher activists, particularly in the context of local educational governance in Pacitan District. Data were collected through a combination of qualitative interviews, questionnaires, and field observations involving teacher activists, local government officials, and school administrators. The analysis considers competencies such as leadership, communication, policy advocacy, and community engagement, evaluating their impacts on policy implementation, curriculum development, and student outcomes. The results indicate that teacher activists in Pacitan District possess high levels of commitment and are well-versed in local educational policies, yet often lack formal training in public administration and policy advocacy. This skill gap limits their capacity to collaborate effectively with the local government in some instances, resulting in missed opportunities for educational improvements. The study also identifies key areas where teacher activists can enhance their competencies to better fulfill their roles. Notable among these are strategic planning, stakeholder engagement, and understanding of government procedures, which are crucial for effective policy advocacy and execution. Strengthening these areas through targeted professional development programs could empower teacher activists to more effectively champion educational causes and influence policy-making at the district level. A significant outcome of this study is the recommendation for a structured, collaborative framework between teacher activists and the local government, with an emphasis on joint decision-making, regular training sessions, and shared objectives. Such a framework could enhance the efficacy of educational policies and ensure that teacher activists’ input is both valued and impactful within the broader educational development agenda of Pacitan District. The study concludes that the competencies of teacher activists significantly influence their ability to cooperate with the local government, impacting educational progress within the district. A mutual understanding of roles, coupled with ongoing professional development, is essential to maximize the potential contributions of teacher activists. This collaborative approach is crucial for driving sustainable educational reforms and fostering a supportive environment for student achievement across Pacitan District schools. Future research should explore the long-term effects of competency-based training on teacher activists' roles and the overall quality of education within similar regional settings, aiming to generalize these findings for broader applicability across Indonesia’s educational landscape.